Foundations of scientific thinking in Islamic tradition: its implications on thought, behaviour, and action - Ahmed Shogar, Ibrahim Adam (Zes Rokman Resources, 2016)
Peace, progress, and development are the terminal goals of human community across the history. Mankind has been adopting various approaches to achieve these crucial objectives. Philosophy, mythology, religion, and science are among the major approaches. The two common aspects of the above goals are knowledge of behaviours of things that necessary to understand the material world, and knowledge of human behaviour that necessary to manage the community. Although, religion has been playing a major role in favour of the later aspect, however, the ‘scientific thinking’ is the most relevant approach to the first aspect, that is, the knowledge of the physical world. Scientific thinking is a mode of systematic inquiry that inspired by the worldview and guided by the common thought of intellectual’s community. The major objective of this paper is to investigate the foundations and historical development of the term ‘scientific thinking’, especially in Islamic tradition, and its role in the progress of human community. The paper investigates both the cognitive (epistemic) and conventional (social) aspects of scientific thinking based on Qur`anic perspective. If modern Muslim communities are facing many challenges, such as radicalism and civil wars, that is the true external picture of their internal thoughts. In other words, they need to rethink about their ideas rather than their actions. Such reflection is necessary to rediscover the foundations of scientific thinking that genuinely implanted by the holy Qur`an in the opening of Islamic civilization; and by virtue of which the Muslim Mummah remained prosperous, progressive, and creative in science and technology, as a leading nation, across eight centuries. Without overlooking the external factors, this article presupposes that the entire problems of modern Muslim communities today are due to the way they think. Nevertheless, the scientific spirit and creative mind in Islamic civilization has lost the ground for other nations since the reflective thought and systematic inquiry, that emphasized by the holy Qur`an, were openly criticized and tempestuously abandoned all together with the speculative philosophy. The paper also highlights the motivational sources and the final goals of scientific thinking in Islamic tradition, and their role in recreating the research spirit. This ‘self-rediscovery’ investigation is essential to address the root causes of the catastrophic condition of Muslim world today and to identifying the strategic methods to overcome the challenge.